AVIM—A contactless system for infant data acquisition and analysis: Software architecture and first results. (July 2015) - Orlandi, Silvia; Guzzetta, Andrea; Bandini, Andrea; Belmonti, Vittorio; Barbagallo, Salvatore D.; Tealdi, Gessica; Mazzotti, Sara; Scattoni, Maria Luisa; Manfredi, Claudia
Highlights: We design a new architecture of a system conceived for supporting clinical diagnosis in newborns. Analysis of acoustical and kinematical parameters for neurodevelopmental assessment with contactless techniques. Unique and flexible system to support clinician from the acquisition of the signals to the results. Appreciable decrease in investigation time, costs and errors for the diagnosis. Abstract: Traditional techniques for the diagnosis of neurological disorders are recently complemented by contact-less methods that provide a semi-quantitative assessment of the patient status. In this framework, the assessment of infant's behaviour based on the analysis of audio and video recordings is appealing thanks to its unobtrusiveness and to the affordable costs of the equipment. This paper presents the architecture of a system, named AVIM, conceived for supporting clinical diagnosis in newborns with contact-less techniques. Its most innovative aspect is the ability of merging in a single tool the management of medical records and reports, audio/video data acquisition, handling and analysis, editing and filling out customized tests. Moreover, unlike other commercial or open source software tools, AVIM allows adding markers and notes while recording audio and video signals and provides detailed reports with both perceptual scores and acoustical and kinematical parameters of clinical interest computed through dedicated innovative techniques. AVIM is therefore a unique and flexible system that could successfully support the clinician during the entire process from the acquisition of the signals to the results. In addition to providing an appreciable decrease in investigation time, costs and errors, AVIM could support the diagnosis integrating clinicians' qualitative analysis, based on subjective skills, with objective measurements. To highlight its capabilities, AVIM is applied here to the management and analysis of personal and clinical data of newborns audio/video recorded in 5 time points from 10 days to the 24th week of age, according to a specific protocol. Patient data, results of customized tests, tables and plots are provided in a user-friendly environment.